Development of Religious Moderation Application Based on Go Moderate Application in Improving the Moderate Attitude of Madrasah Aliyah Students - Bayu Bambang Nurfauji; Tedi Priatna; Erni Haryanti; Ratu Suntiah; Rifa Rizqiyani (Edunity Kajian Ilmu Sosial dan Pendidikan, 2025)
This study is motivated by the strategic role of Madrasah Aliyah (Islamic senior high schools) as educational institutions in instilling the values of religious moderation among students in the digital era. Although religious moderation has become an essential component in strengthening national character, the learning process in madrasahs still faces significant challenges, such as the limited availability of interactive learning media and the underutilization of digital technology in education. The objectives of this research are to: (1) analyze the need for a digital-based religious moderation application, (2) design an application model, (3) develop the application, (4) implement the application in learning activities, (5) conduct evaluations, (6) test its validity, and (7) assess the impact of its use. The research method employed is Research and Development (R&D), using the ADDIE development model, with data collection techniques including interviews, document analysis, questionnaires, observations, and tests. The research subjects were students at MAN 2 and MAN 3 Cianjur Regency. The findings reveal that the needs analysis indicates the necessity for digital learning media that support the development of moderate attitudes. The application was developed in mobile format, with a design flow based on flowcharts and storyboards. Implementation of the application at MAN 2 Cianjur yielded a score of 3.83 (categorized as very good), while at MAN 3 Cianjur it scored 3.66 (categorized as good). The formative evaluation indicates that the application is effective, practical, and has a positive impact. The GO MODERATE application represents a strategic innovation in religious moderation education that is contextual and aligned with the characteristics of the digital generation.